Motivation in seeking mentoring and developing self-determination among college students - Lactao, James L.
Mentees take the initiative to seek out their mentors when two conditions are met , namely, a developed relationship, and a high level of need. Specifically, the study shows that (1) deliberate effort from both mentors and mentees is necessary to make the mentoring relationship grow and mature (i.e. clear the path, pave the road, and cement the relationship); and (2) the mentees do not hesitate to go to their mentors whenever there are needs that they have to fulfill. Twelve university students studying in a private, nonsectarian university shared their lived experiences in initiating mentoring sessions with their mentors through a semi-structured interview. This study explored these students’ lived experiences in mentoring and their motivations for seeking out their mentors. Data were analyzed through the lenses of two sub-theories of Self-determination Theory, namely, the Organismic Integration Theory (OIT) and Basic Psychological Needs Theory (BPNT). The results demonstrate that the most dominant motivations in seeking out mentoring are identified and integrated regulations, which are two of the four major types of motivational regulation as theorized in OIT. Identified regulation happens when mentees consciously value the mentoring-seeing behavior, while integrated regulations happens when mentees maintain a sense of congruence, synthesis, and consistency in their behaviors. At the same time, mentoring relationships as experienced by the students provide opportunities for their growth and development in the basic psychological needs of competence, autonomy, and relatedness according to the BPNT framework. This study recommends educational institutions, educational psychologists, and other professionals involved in education to consider implementing mentoring programs that consider relationship-building and addressing the needs of mentees.